1992
DOI: 10.1007/bf00399935
|View full text |Cite
|
Sign up to set email alerts
|

The sympathetic response to euglycaemic hyperinsulinaemia

Abstract: Summary. Sympathetic nervous system activation by insulin has been suggested as a mechanism explaining the association between insulin resistance and hypertension. We further examined the effect of insulin by direct microneurographic muscle and skin nerve sympathetic activity recordings during euglycaemic insulin clamps in healthy subjects. The mean plasma insulin level was elevated from 5.3 + 0.7 to 92.2 + 2.2 mU/1 in seven subjects during a 90-min one-step clamp. In six other subjects plasma insulin was furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(69 citation statements)
references
References 48 publications
3
64
0
2
Order By: Relevance
“…Despite this sympathetic excitation, forearm vascular resistance fell and mean arterial pressure did not rise. Berne et al 21 also reported that insulin increased muscle sympathetic nerve activity and plasma norepinephrine without significant changes in arterial pressure.…”
Section: The Vasodilator Action Of Insulinmentioning
confidence: 94%
See 2 more Smart Citations
“…Despite this sympathetic excitation, forearm vascular resistance fell and mean arterial pressure did not rise. Berne et al 21 also reported that insulin increased muscle sympathetic nerve activity and plasma norepinephrine without significant changes in arterial pressure.…”
Section: The Vasodilator Action Of Insulinmentioning
confidence: 94%
“…Morgan and colleagues have reported that hyperinsulinemia increased lumbar sympathetic nerve activity but not renal or adrenal sympathetic nerve activity in normotensive Sprague-Dawley (unpublished observations) or WistarKyoto rats. 32 In humans, Berne et al 21 have reported that hyperinsulinemic clamp increases sympathetic nerve activity to muscle but not to skin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because these factors have been shown to increase energy expenditure (EE) and reduce energy intake (EI) (9)(10)(11)(12)(13), their decrease with fat loss is certainly detrimental to the maintenance of weight stability in the reduced-obese state. Because fat oxidation seems to be dependent upon P-adrenergic stimulation (14,15), the decrease in SNS activity is especially problematic in the context that obese and formerly obese individuals seem to have a preference for this macronutrient (1 6,17).…”
Section: Introductionmentioning
confidence: 99%
“…The liver (12), the autonomic nervous system (19), and the hypothalamus (10, II) have been proposed as sites of the anorexic action of insulin. Although there is evidence that insulin increases sympathetic nervous activity (20)(21)(22), the connection to appetite suppression remains hypothetical. Recent experiments with the ob gene have demonstrated increased ob gene expression in adipose tissue after insulin injection in rats, which would represent another peripheral action of insulin (23).…”
Section: Introductionmentioning
confidence: 99%